Aksentuasi Kepentingan terbaik Anak dalam Putusan Nafkah sebagai Upaya Penjaminan Hak Asasi Anak - M. Nur Syafiuddin (Jurnal HAM, 2022)
Children have an important positioning in spheres of human life, starting from the scope of family life to the state, therefore every policy must be able to guarantee the fulfillment of children's rights. This study aims to describe the guarantee of children's human rights through the accentuation of the best interests of children in the decision to make a living. The result of the study is useful as a basis for adaptive thinking for judges in making decisions for children's livelihoods that prioritize the best interests of children. This study uses normative legal research with a philosophy and legislation approach, and a prescriptive analysis method. The accentuation of the best interests of the child in the judge's decision regarding livelihoods must be able to lead to guarantee of the rights of the child's welfare which includes three aspects, namely the presence of parents, condition (maturity and experience) and the environment in which the child lives. The advice given is to remember that living is one of the needs of children to fulfill their natural rights in order to survive and improve their quality of life, so judges should always conduct in-depth studies (ijtihad) in every examination of children's livelihood cases.